Improving the Ability of Art Using 3M Activities (Drawing, Trying, Sticking) Children Group A Thia Ananda Playing Group - Tuti Purwanti; Mardiana Sari; Syarwani Ahmad (Journal on Education, 2024)
This study aims to determine the Improvement of Fine Art Skills by Using 3M Activities (Drawing, Tear, Sticking) Children in Group A Thia Ananda Play Group. The research location was carried out at the Thia Ananda Play Group, which is located at Jalan Cendana 2 Lorong Asabri 2 RT 22 RW 04 Sambirejo Village, Mariana Village, Banyuasin I District, Banyuasin Regency. The subjects in this study were the children of the Thia Ananda Play Group, namely group A, namely out of 10 children divided into 6 girls and 4 boys. The research uses quantitative and qualitative methods with an action research model according to Kemmis and Taggart which focuses on children's visual arts abilities.The results of the study were an increase in the average level of achievement in the development of children's art skills in group A from the pre-cycle to cycle I and to cycle II, namely that in the pre-cycle the score was 18.8 in the undeveloped category, then in cycle I with a score of 29, 2 with the starting to develop category experienced an increase of 10.4 while in cycle II with a score of 41.8 with the developing category according to expectations this shows that cycle II experienced an increase of 12.6, so it was concluded at the end of cycle II, the research was said to be successful because the success criteria have been achieved according to the agreement of the researcher and the collaborator.